2015
DOI: 10.1371/journal.pgen.1005383
|View full text |Cite
|
Sign up to set email alerts
|

TFIIS-Dependent Non-coding Transcription Regulates Developmental Genome Rearrangements

Abstract: Because of their nuclear dimorphism, ciliates provide a unique opportunity to study the role of non-coding RNAs (ncRNAs) in the communication between germline and somatic lineages. In these unicellular eukaryotes, a new somatic nucleus develops at each sexual cycle from a copy of the zygotic (germline) nucleus, while the old somatic nucleus degenerates. In the ciliate Paramecium tetraurelia, the genome is massively rearranged during this process through the reproducible elimination of repeated sequences and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(54 citation statements)
references
References 79 publications
3
50
0
1
Order By: Relevance
“…Finally, we asked how extensively IESs that accumulated in the MA lines’ somatic genome overlap with IESs that are epigenetically controlled in the control stock 51 (Lhuillier-Akakpo et al 2014; Sandoval et al 2014; Maliszewska-Olejniczak et al 2015) . We found that a significant excess of the IESs that are retained in the MA lines fall into a class of IESs that are under the control of small RNAs (epi-IESs) in stock 51 ( Figure S5 ).…”
Section: Resultsmentioning
confidence: 99%
“…Finally, we asked how extensively IESs that accumulated in the MA lines’ somatic genome overlap with IESs that are epigenetically controlled in the control stock 51 (Lhuillier-Akakpo et al 2014; Sandoval et al 2014; Maliszewska-Olejniczak et al 2015) . We found that a significant excess of the IESs that are retained in the MA lines fall into a class of IESs that are under the control of small RNAs (epi-IESs) in stock 51 ( Figure S5 ).…”
Section: Resultsmentioning
confidence: 99%
“…The C2H2 zinc finger present in both mtGa and mtGb is predicted to bind GCTA or GCTT, suggesting that direct binding to IESs is required for correct excision. We currently cannot exclude the possibility that mtG proteins bind to the TFIIS4-dependent nascent transcripts found to play a role in IES excision ( 15 ), rather than to DNA itself. In both cases, the co-localization of mtGa-GFP and H3K9me3 marks in what appears to be DNA elimination structures would suggest that binding is maintained until excision.…”
Section: Discussionmentioning
confidence: 99%
“…After being loaded on the Piwi proteins Ptiwi01 and Ptiwi09 ( 12 , 13 ), scnRNAs are imported into the parental MAC and those able to pair with pervasive nascent transcripts are somehow inactivated ( 14 ). Thus, only those originating from MIC-specific sequences would be licensed to later target the same sequences in the developing zygotic MAC, by pairing with TFIIS4-dependent nascent transcripts ( 15 ). In both parental and zygotic MACs, pairing of scnRNAs with nascent transcripts is thought to involve the RNA-binding and Ago-hook-containing proteins Nowa1/2 ( 16 , 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…A large, but as of yet undetermined, number of non-coding RNAs (ncRNAs) have recently been uncovered. We, along with other groups, have demonstrated that these ncRNAs can regulate normal development and disease occurrence through controlling RNA maturation and protein synthesis 6 - 12 . Notably, the number of ncRNAs is more than that of protein-coding genes within the genome 13 , 14 .…”
Section: Introductionmentioning
confidence: 94%